The Relationship Between Physical Activity and Quality of Life Among Outpatient Patients with Schizophrenia at Sambang Lihum Psychiatric Hospital - Syamsiar; Sukmawati; Rauf, Suriani (Fakultas Kedokteran, Universitas Papua, 2025)
Outpatients with schizophrenia frequently experience a decline in quality of life due to disease-related symptoms, medication side effects, and limitations in social functioning. Physical activity has the potential to serve as a non-pharmacological intervention that supports patient recovery. This study aimed to analyze the relationship between physical activity and quality of life among outpatient patients with schizophrenia at Sambang Lihum Psychiatric Hospital. This quantitative study employed a cross-sectional design with purposive sampling involving 96 respondents. Physical activity was assessed using the International Physical Activity Questionnaire (IPAQ), while quality of life was measured using the Indonesian Modification of Subjective Well-Being Under Neuroleptics (IM-SWN). The results showed that the majority of respondents had a high level of physical activity (60.4%) and an adequate quality of life (79.2%). Spearman’s correlation analysis revealed a significant positive relationship between physical activity and quality of life (ρ = 0.582; p = 0.001). These findings indicate that higher levels of physical activity are associated with better quality of life. Therefore, physical activity should be positioned as a potential non-pharmacological intervention that is integrated into outpatient care, rather than merely as a supporting factor, in order to sustainably improve the quality of life of patients with schizophrenia.